The flipped classroom in medical education: A new standard in teaching. (February 2022) - Phillips, Jessica; Wiesbauer, Franz
Abstract: Many medical educators, out of necessity imposed by the COVID-19 pandemic, had to flip their classrooms. However, instead of adapting to this new teaching style, many have proceeded in the manner that they have always used to create content, opening a slide deck and inserting content until they are satisfied with the result. When in fact, we know based on evidence and our own experience, that educators should first plan, organize, and storyboard before collecting information into a presentation [1, 2]. If educators need to replace real-world teaching and interaction, we believe the next best option is video education, although there are other forms of prework that can be utilized to flip medical classrooms, including short readings and exercises. We discuss the case for flipping medical classrooms, the limitations, and how educators can get started flipping their classrooms today.